KETERLIBATAN PROFESIONAL IBU PEKERJA DALAM DINAMIKA DIGITAL ROLE CONFLICT, CYBER FATIGUE, WORKLOAD, DAN BOUNDARY MANAGEMENT SKILLS DENGAN EMOTIONAL AGILITY - Robin, Robin; Br Simamora, Rusdiana; Hidayat, Ferry (Penerbit Lafadz Jaya, 2025)
The digital era presents new challenges for working mothers in the formal sector, who face the complexity of multiple roles. On the one hand, they are required to demonstrate high performance and adapt to technology-based work systems, while on the other hand, family responsibilities remain a top priority. This situation often leads to digital role conflict, cyber fatigue, and excessive workload, which ultimately have a negative impact on work engagement. This study aims to analyze the influence of digital role conflict, cyber fatigue, workload, and boundary management skills on work engagement, with emotional agility as a moderating variable. The research employed a quantitative approach with an explanatory design. The sample consisted of 200 working mothers in the formal sector in Medan City, selected using the Lemeshow formula. Data were collected through a five-point Likert scale questionnaire and analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results indicate that digital role conflict (β = -0.31; p = 0.004), cyber fatigue (β = -0.27; p = 0.012), and workload (β = -0.22; p = 0.028) have a significant negative effect on work engagement. In contrast, boundary management skills (β = 0.37; p = 0.000) and emotional agility (β = 0.30; p = 0.001) show a significant positive effect. Moreover, emotional agility was found to play a moderating role that strengthens work engagement amid digital pressures.